Spermatotoxic, cytotoxic and genotoxic evaluation of aqueous extract of Ocimum gratissimum in albino mice (Open Access Journal of Medicinal and Aromatic Plants, 2013)
Ocimum gratissimum (Lamiaceae) is an alternative medicine as well as food condiment in African and Asian countries. Information on its safe consumption is important considering its wide utilization. The potential effects of aqueous extract of this plant on cell division, chromosome structure and sperm morphology in mice were investigated. The Inductions of chromosomal aberrations and abnormal sperm cells were not dose dependent. However, these were and sperm morphology tests, respectively. Aberrant sperm cell in form of tail folded over head was observed most. These observations suggest possible mutagenic activity of the aqueous extract of O. gratissimum in albino mice. Â Key words: Ocimum gratissimum, chromosome, mitotic index, sperm cells, aqueous extract Â Â